4EBP1/eIF4E and p70S6K/RPS6 axes play critical and distinct roles in hepatocarcinogenesis driven by AKT and N‐Ras proto‐oncogenes in mice. Issue 1 (25th November 2014) - Wang, Chunmei; Cigliano, Antonio; Jiang, Lijie; Li, Xiaolei; Fan, Biao; Pilo, Maria G.; Liu, Yan; Gui, Bing; Sini, Marcella; Smith, Jeffrey W.; Dombrowski, Frank; Calvisi, Diego F.; et al.
<x xml:space="preserve">Abstract</x> Concomitant expression of activated forms of v‐akt murine thymoma viral oncogene homolog (AKT) and Ras in mouse liver (AKT/Ras) leads to rapid tumor development through strong activation of the mammalian target of rapamycin complex 1 (mTORC1) pathway. mTORC1 functions by regulating p70S6K/ribosomal protein S6 (RPS6) and eukaryotic translation initiation factor 4E‐binding protein 1/ eukaryotic translation initiation factor 4E (4EBP1/eIF4E) cascades. How these cascades contribute to hepatocarcinogenesis remains unknown. Here, we show that inhibition of the RPS6 pathway by rapamycin effectively suppressed, whereas blockade of the 4EBP1/eIF4E cascade by 4EBP1A4, an unphosphorylatable form of 4EBP1, significantly delayed, AKT/Ras‐induced hepatocarcinogenesis. Combined treatment with rapamycin and 4EBP1A4 completely inhibited AKT/Ras hepatocarcinogenesis. This strong antineoplastic effect was successfully recapitulated by ablating regulatory associated protein of mTORC1, the major subunit of mTORC1, in AKT/Ras‐overexpressing livers. Furthermore, we demonstrate that overexpression of eIF4E, the proto‐oncogene whose activity is specifically inhibited by 4EBP1, resulted in hepatocellular carcinoma (HCC) development in cooperation with activated Ras. Mechanistically, we identified the ectonucleoside triphosphate diphosphohydrolase 5/ adenylate kinase 1/cytidine monophosphate kinase 1 axis and the mitochondrial biogenesis pathway as targets of the 4EBP1/eIF4E cascade in AKT/Ras and Ras/eIF4E livers as well as in human HCC cell lines and tissues. Conclusions: Complete inhibition of mTORC1 is required to suppress liver cancer development induced by AKT and Ras proto‐oncogenes in mice. The mTORC1 effectors, RPS6 and eIF4E, play distinct roles and are both necessary for AKT/Ras hepatocarcinogenesis. These new findings might open the way for innovative therapies against human HCC. (Hepatology 2015;61:200–213)